Report of the forth Asian Prostate Cancer (A-CaP) study meeting - Youl Lee, Ji; Taniguchi, Tomotaka; Zhang, Kai; Ng, Chi Fai; Hakim, Lukman; Umbas, Rainy; Kim, Choung-Soo; Chung, Byung Ha; Kim, Wun-Jae; Ong, Teng Aik; Lim, Jasmine; Akaza, Hideyuki (Oxford University Press, 2019)
The Asian Prostate Cancer (A-CaP) Study is an Asia-wide prospective registry study for surveying the treatment outcome of prostate cancer patients who have received a histopathological diagnosis. The study aims to clarify the clinical situation for prostate cancer in Asia and use the outcomes for the purposes of international comparison. Following the first meeting in Tokyo on December 2015, the second meeting in Seoul, Korea 2016, the third meeting in Chiang Mai, Thailand, on October 2017, the fourth meeting was held in Seoul, again on August 2018 with the participation of members and collaborators from 13 countries and regions. In the meeting, participating countries and regions presented the current status of data collection and the A-CaP office presented a preliminary analysis of the registered cases received from each country and region. Participants discussed ongoing challenges relating to data cleaning and data updating which is the next step of the A-CaP study following the data collection phase between 2016 and 2018. There was specific difference in term of the patient characteristics, and initial treatment pattern among East Asia, Southeast Asia and Turkey, and Jordan. Finally, a close relationship between prevalence of PSA test and disease stage of the patients at diagnosis in Japan and Malaysia was discussed.